Inquiry Learning Model Based on Traditional Games for Indonesian Children in Improving Storytelling Ability - Khasanah, Siti; Kusmana, Suherli; Wilsa, Jaja (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to explain the inquiry learning model based on traditional Indonesian games in improving children's storytelling abilities, as well as the process of implementing it in learning. The research was conducted in the 2023/2024 Academic Year, Even Semester at Madrasah Ibtidaiyah Al-Zaytun, Sandrem Village, Gantar District, Indramayu Regency, on class IV (four) students in West Java Province. This study uses the Research and Development (R&D) method with the Analysis Design Development Implementation and Evaluation (ADDIE) model. The data collection method, in the form of interviews, questionnaires, and observations, is a new learning model developed from the traditional game-based inquiry learning model to improve storytelling to make learning more meaningful. The results of the assessment of the traditional game-based learning model design were 90%, with the category very suitable for use. The results of the learning media expert assessment of 96% showed that learning media is very suitable for use. Meanwhile, Based on the implementation results, the assessment result is 94%. This proves that the learning model is suitable for use. Based on the data above, a traditional game-based inquiry learning model for improving storytelling abilities in fourth-grade elementary school students is needed